Specialization of derivations in modal logic S5 - Pliuškevičienė, Aida (Lietuvos matematikos rinkinys, 2023)
Loop-check-free decidable specialization of sequent calculus for modal logic S5 is presented. Soundness and completness of this calculus is proved.
Keywords: modal logic; sequent calculus; decidable calculus; loop-check